2010
DOI: 10.3844/ajassp.2010.1200.1209
|View full text |Cite
|
Sign up to set email alerts
|

Differences in Soil Physical and Chemical Properties of Rehabilitated and Secondary Forests

Abstract: Problem statement:The soil properties of tropical rain forest in Southeast Asia have been characterized by several researchers; however empirical data on soil characteristics under rehabilitation program are still limited or even lacking. This research is important to determine the soil physical and chemical properties of a rehabilitated degraded forest land 19 years after planting with various indigenous species in comparison with adjacent secondary forests and to elucidate the soil fertility status in rehabi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

9
28
0

Year Published

2013
2013
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 33 publications
(37 citation statements)
references
References 26 publications
9
28
0
Order By: Relevance
“…Such similar trend was also reported where higher number of large trees over 30 cm dbh will contribute to the higher aboveground biomass and carbon for primary forest when compared to the secondary forest in Singapore (Ngo et al 2013). Furthermore, this could be due to the effect of higher site fertility index at similar site as reported by Akbar et al (2010) compared to other study plots.…”
Section: Resultssupporting
confidence: 73%
“…Such similar trend was also reported where higher number of large trees over 30 cm dbh will contribute to the higher aboveground biomass and carbon for primary forest when compared to the secondary forest in Singapore (Ngo et al 2013). Furthermore, this could be due to the effect of higher site fertility index at similar site as reported by Akbar et al (2010) compared to other study plots.…”
Section: Resultssupporting
confidence: 73%
“…The resultfrom this study also showed that there was low accumulation of organic matter after planting. After harvesting or clearing, organic matter from the soil decreased because of no input of organic matter from the plant since it was harvested (Akbar et al, 2010). Similar results were reported by Nye and Greenland (1964); Kedawang et al (2004) and Ilstedt et al (2004); soil organic matter decline rapidly after the soil is exposed due to harvesting or clearing activities.…”
Section: Ajessupporting
confidence: 77%
“…The acidity occurring in the forest soils was due to the presence of Al and H. According to Zaidey et al (2010), the Al concentrations and organic matter influenced the soil acidity. Moreover, the acidity may be caused by water deficiency due to drought (Akbar et al, 2010). When this occur, root mat develop on the surface layer resulting in high carbon content.…”
Section: Ajesmentioning
confidence: 99%
“…The CEC recorded in this study was very low with a value of 3.94 cmol c kg -1 soil which was due to low clay content and similar to other study found by (Malisa et al, 2011;Roslan et al, 2011) reported that the CEC values on a BRIS soil less than 5 cmol c kg -1 .This means that the bases are easily lost via leaching during rainy season. This is similar to Akbar et al (2010) who reported that different in CEC values due to soil erosion or leaching. Parfitt et al (1995) also reported that lower contents of clay and loam in the soil lead to a low CEC values.…”
Section: Initial Properties Of the Soilsupporting
confidence: 80%